Rituals of Female (Dis)Empowerment: Baptism in the Context of Conversion in Medieval German Literature (Eventum: A Journal of Medieval Arts & Rituals, 2024)
This article focuses on the interplay between and the ambiguity of female empowerment and disempowerment in female conversions to Christianity in Middle High German literary texts. With regards to gender, the ritual of baptism is of interest in several respects. Gender and genderlessness, sexuality, and desire, as well as nudity and shame, play a crucial role in baptism, as the ceremony is linked to the Fall of Man and involves ritual nudity. Although the conversion to Christianity by means of baptism in biblical terms (Gal. 3:27–28) erases gender, race, and social status, the Christian practice of baptism is asymmetrical regarding gender because usually only men administer the sacrament, whereas women merely receive it. Moreover, in medieval German literature, male power or romantic interests are often the driving force behind women’s conversions. By examining different versions of Saint Thecla’s legend, the conversion of Arabel-Gyburc to Christianity in Ulrich von dem Türlin’s Arabel, conversion as temptation in Rudolf von Ems’ Barlaam und Josaphat, and the juxtaposition of two female conversions in Salman und Morolf, it becomes clear that female agency and lack or loss of power often go hand in hand and are, in fact, inseparable in literary representations of conversions. From the perspective of gender, the baptism ritual is hence characterized by ambiguity and figures as a ritual of female empowerment and disempowerment alike.
Keywords: baptism; christening; gender; ritual nudity; shame; temptation; desire; Middle High German